Kinematic differences between the dominant and nondominant legs during a single-leg drop vertical jump in female soccer players - Nakahira, Y.; Taketomi, S.; Kawaguchi, K.; Mizutani, Y.; Hasegawa, M.; Ito, C.; Uchiyama, E.; Ikegami, Y.; Fujiwara, S.; Yamamoto, K.; Nakamura, Y.; Tanaka, S.; et al. (The American Journal of Sports Medicine, 2022)
Background: In soccer, the roles of the dominant (kicking) and nondominant (supporting) legs are different. The kinematic differences between the actions of the dominant and nondominant legs in female soccer players are not clear.